Impact Evaluation of an Incentive Program on Educational Achievement of Indigenous Students - Uwe Dulleck; Juliana Silva-Goncalves; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2014)
This article introduces the Fogs Artie program that attempts to close the gap in educational attainment between Indigenous and non-Indigenous Australians, and provides an evaluation of its effectiveness. The program is of special interest as it uses in-kind incentives conditional on achievement of a specific target for academic grades, behaviour and attendance, coupled with information sessions on the importance of educational achievement. In 2012, all Indigenous students enrolled in 21 high schools in Queensland were invited to take part in the program. Using a differences-in-differences strategy, we find that the program improved behavioural and academic grades and reduced the number of unexplained absences for female students, but not for male students. In contrast, the program improved scores on a standardized national assessment test for male students. Moreover, we find that the program is only effective for students from intact families.
Keywords: I24; I25; I28; 330; Education; Incentives; Indigenous; Program Evaluation; Policy